Cedrus atlantica pollen morphology and investigation of grain size variability using laser diffraction granulometry. (3rd July 2018) - Bell, Benjamin A.; Bishop, Thomas H.; Fletcher, William J.; Ryan, Peter; Ilmen, Rachid
ABSTRACT: The morphology and size variability of pollen grains of Cedrus atlantica were investigated using a novel approach employing laser diffraction granulometry. We provide new insights into size variability and present high-quality light microscopy (LM) and scanning electron microscopy (SEM) imagery of Cedrus atlantica pollen. Grains have an average size of 59.1 ± 4.0 µm, measured on millions of grains from 91 samples. Analysis showed there is high variability of grain size within individual samples, although variability between samples is not significant. We found no significant relationships between grain size and climate (including temperature, precipitation and aridity), and suggest that grain size of fossil Cedrus pollen would not be a good proxy for climate reconstruction. Grain size may be influenced by a number of complex factors such as genome size or adaptations to support wind pollination, while variability within individual samples may result from the irregular development of pollen. The laser diffraction method produced repeatable, robust measurements on millions of pollen grains which are highly correlated with measurements taken using LM ( r = 0.91, p = 0.002). Where grain size information is crucial for pollen identification, for developing isolation techniques for geochemical analysis, for investigating climatic and environmental influence, or for investigating links between genomes and grain size, particle size analysis by laser diffraction provides a reproducible and robust method for quickly determining pollen grain size on many samples.